2022
DOI: 10.3389/fcvm.2022.843837
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing Identifies a Novel Variant (c.1538T > C) of TNNI3K in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: BackgroundsArrhythmic right ventricular cardiomyopathy (ARVC) is a cardiomyopathy with a genetic predisposition that can lead to a sudden cardiac death and heart failure. According to the 2010 Task Force Criteria, genetic diagnosis is one of the most important methods, but, so far, only a few genes related to ARVC have been identified.MethodsIn this study, the pathogenic gene of a patient with ARVC was examined using whole-exome sequencing. The plasmids of TNNI3K were constructed, and the effects of the TNNI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…An article suggested that RyR2 should be removed from the causative genes for ACM as more clinical data suggest that it belongs to the CPVT-related field [ 7 ]. However, in addition to this article, there have been some recent articles suggesting that variants in RyR2 -associated genes, such as TNNI3K , may be associated with ACM [ 50 ]. In addition, the gene variants expressed in our manuscript that affect Ca 2+ release following alterations in Ca 2+ channels are also relevant to RyR2.…”
Section: Abnormalities Of Ion Channel Proteins On the Endoplasmic/sar...mentioning
confidence: 99%
“…An article suggested that RyR2 should be removed from the causative genes for ACM as more clinical data suggest that it belongs to the CPVT-related field [ 7 ]. However, in addition to this article, there have been some recent articles suggesting that variants in RyR2 -associated genes, such as TNNI3K , may be associated with ACM [ 50 ]. In addition, the gene variants expressed in our manuscript that affect Ca 2+ release following alterations in Ca 2+ channels are also relevant to RyR2.…”
Section: Abnormalities Of Ion Channel Proteins On the Endoplasmic/sar...mentioning
confidence: 99%
“…A significant positive correlation between TNNI3K mRNA levels and electrocardiography (ECG) PR interval duration has been reported in patients with supraventricular tachyarrhythmias [ 8 , 9 ]. Genetic variants L513P, G526D, T539A, and E768K all reduce the kinase activity of TNNI3K, identified in patients with cardiomyopathies and arrhythmias [ 10 , 11 , 12 ]. Enigmatically, a common single nucleotide polymorphism (SNP), I686T (rs3737564), that is present in up to 4% of human populations, reduced autophosphorylation and kinase activity of TNNI3K in vitro [ 13 ], implying potential effects of this kinase in cardiac diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, 7 TNNI3K (troponin-I interacting kinase) variants have been reported, 1–7 from which 3 with moderate-to-strong genetic evidence, for example, multigenerational cosegregation. 1,2,4 Patients harboring variants in TNNI3K present with several cardiac phenotypes including dilated cardiomyopathy (DCM), cardiac conduction disease (CCD), and supraventricular tachycardias (SVT).…”
mentioning
confidence: 99%
“…However, the evidence linking TNNI3K to human cardiac disease has thus far remained limited to family reports, some with limited genetic evidence. 1–7…”
mentioning
confidence: 99%
See 1 more Smart Citation